REFINE (REducing Falls in In-patieNt Elderly) using bed and bedside chair pressure sensors linked to radio-pagers in acute hospital care: a randomised controlled trial - Sahota, Opinder; Drummond, Avril E.R.; Kendrick, Denise; Grainge, Matthew J.; Vass, Catherine; Sach, Tracey; Gladman, John R.F.; Avis, Mark (Oxford University Press, 2014)
Background: falls in hospitals are a major problem and contribute to substantial healthcare burden. Advances in sensor technology afford innovative approaches to reducing falls in acute hospital care. However, whether these are clinically effective and cost effective in the UK setting has not been evaluated.